Cost-effectiveness of nurse practitioners in primary and specialised ambulatory care: systematic review. Issue 6 (8th June 2015) - Martin-Misener, Ruth; Harbman, Patricia; Donald, Faith; Reid, Kim; Kilpatrick, Kelley; Carter, Nancy; Bryant-Lukosius, Denise; Kaasalainen, Sharon; Marshall, Deborah A; Charbonneau-Smith, Renee; DiCenso, Alba
Abstract : Objective: To determine the cost-effectiveness of nurse practitioners delivering primary and specialised ambulatory care. Design: A systematic review of randomised controlled trials reported since 1980. Data sources: 10 electronic bibliographic databases, handsearches, contact with authors, bibliographies and websites. Included studies: Randomised controlled trials that evaluated nurse practitioners in alternative and complementary ambulatory care roles and reported health system outcomes. Results: 11 trials were included. In four trials of alternative provider ambulatory primary care roles, nurse practitioners were equivalent to physicians in all but seven patient outcomes favouring nurse practitioner care and in all but four health system outcomes, one favouring nurse practitioner care and three favouring physician care. In a meta-analysis of two studies (2689 patients) with minimal heterogeneity and high-quality evidence, nurse practitioner care resulted in lower mean health services costs per consultation (mean difference: −€6.41; 95% CI −€9.28 to −€3.55; p<0.0001) (2006 euros). In two trials of alternative provider specialised ambulatory care roles, nurse practitioners were equivalent to physicians in all but three patient outcomes and one health system outcome favouring nurse practitioner care. In five trials of complementary provider specialised ambulatory care roles, 16 patient/provider outcomes favouring nurse practitioner plus usual care, and 16 were equivalent. Two health system outcomes favoured nurse practitioner plus usual care, four favoured usual care and 14 were equivalent. Four studies of complementary specialised ambulatory care compared costs, but only one assessed costs and outcomes jointly. Conclusions: Nurse practitioners in alternative provider ambulatory primary care roles have equivalent or better patient outcomes than comparators and are potentially cost-saving. Evidence for their cost-effectiveness in alternative provider specialised ambulatory care roles is promising, but limited by the few studies. While some evidence indicates nurse practitioners in complementary specialised ambulatory care roles improve patient outcomes, their cost-effectiveness requires further study.